Human Resources Management in the European Context - Ion PETRESCU; Camelia KONRAD (Revista de Management Comparat International)
Human resources management has a central place within European management. The European Union’s demands are continuously increasing, asking more and more from human resources management in terms of knowledge, studying and generalization of experience, in the field of ordered development by using specific European methods and rules, and following the reflected results in the profits and the human resources’ state of satisfaction.